(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article covers important issues in preparing young people for a family through the research of scientists, and it is stated that a comprehensive study of the psychological readiness of young people for family life, special scientific research is of urgent importance.